(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This study was done on two years of field trials for determining traits explaining the most of diversity among twenty nine barley landraces in presence of three controls and also to confirm the relationships between the different traits studied. Via these two experiments, phenology and agro-morphological traits at maturity were studied. Results of the tests showed a great variability within the germplasm revealed by very highly significant differences (P‹0.001) between genotypes for all traits considered and statistically analyzed. Principal component analyzes could explain more than 70 % of the total variation and the greatest variability was explained over the two years by the common following traits: days to heading, days to maturity, 1000 grain weight, awn length, spike weight and plant height. Very high correlations existing between the following traits: awn length, 1000 grain weight, spike weight, days to heading and days to maturity, were confirmed through each test. Also, correlations existed between plant height, 1000 grain weight, spike weight, days to heading and days to maturity and between plant height and spike length and also between grain number per spike and spikelet number per spike. Through both seasons, cluster analyzes divided all six-rowed barley into three cluster groups.